Design and implementation of a Vision-Based Air Hockey robot - Abdelrahman Baba; Maysem Mousa (My University, 2022)
In the past decade, robotics revolution has garnered significant attention by researchers and companies because of their ability to perfume human-tasks with better efficiency and higher speed. because of this rapid acceleration in the industry, new robots were developed to do non-critical applications like playing games against humans. Air hockey is one of the most well-known arcade table games, in which, two players try to strike a buck into the opponent’s goal. This project proposes the design and implementation of Vision-Based Air-Hooky playing robot. the robot can move in two dimensions which enables it to do more complex movements which was impossible to do in a single dimension. also it has two playing strategies (defense and attack) to give the player more exciting human-like game play. The table used for this project was designed and built from scratch to meet this project needs.The plastic parts were 3d-printed and can be used to any CNC-based system. The robot itself can be detached from the table without much effort so it can be used as a normal air-hockey table. wireless scoreboard system using ESP module is also available to make it easier for arcade halls to adapt this project as a standard arcade game.a spacial camera with high FPS rate was used to achieve the high speed response needed by this real-time application. an Arduino micro-controller was used to process the output of the camera and handle the movement of the motors.